When Daddy Stalks Mommy: Experiences of Intimate Partner Stalking and Involvement of Social and Legal Authorities When Stalker and Victim Have Children Together. (November 2019) - Løkkegaard, Sille Schandorph; Hansen, Nina Beck; Wolf, Nele Marie; Elklit, Ask
This study examined intimate partner stalking experienced by 196 mothers stalked by the father of their children. Respondents completed a questionnaire concerning experiences of stalking and level of support by the authorities. Results revealed higher rates of harassing than violent stalking. In many cases, the children were also targeted by the stalking. Encounters with several agencies were common, but respondents were often not recognized as victims of stalking and demoralized by extensive case proceedings. This study calls for a special sensitivity of professionals encountering stalked parents in their work and highlights a need for coordination and cooperation among multiple agencies.